G Protein-Coupled Receptor Heteromers as Putative Pharmacotherapeutic Targets in Autism - DelaCuesta-Barrutia, Jon; Peñagarikano, Olga; Erdozain, Amaia M. (Frontiers in Cellular Neuroscience, 2020)
A major challenge in the development of pharmacotherapies for autism is the failure to identify pathophysiological mechanisms that could be targetable. The majority of developing strategies mainly aim at restoring the brain excitatory/inhibitory imbalance described in autism, by targeting glutamate or GABA receptors. Other neurotransmitter systems are critical for the fine-tuning of the brain excitation/inhibition balance. Among these, the dopaminergic, oxytocinergic, serotonergic and cannabinoid systems have also been implicated in autism and thus represent putative therapeutic targets. One of the latest breakthroughs in pharmacology has been the discovery of G protein-coupled receptor (GPCR) oligomerization. GPCR heteromers are macromolecular complexes composed of at least two different receptors, with biochemical properties that differ from those of their individual components, leading to the activation of different cellular signaling pathways. Interestingly, heteromers of the above mentioned neurotransmitter receptors have been described (e.g. mGlu2-5HT2A, mGlu5-D2-A2A, D2-OXT, D2-5HT2A, D1-D2, D2-D3, OXT-5HT2A). We hypothesize that differences in the GPCR interactome may underlie the etiology/pathophysiology of autism and could drive different treatment responses, as has already been suggested for other brain disorders such as schizophrenia. Targeting GPCR complexes instead of monomers represents a new order of biased agonism/antagonism that may potentially enhance the efficacy of future pharmacotherapies. Here, we present an overview of the crosstalk of the different GPCRs involved in autism and discuss current advances in pharmacological approaches targeting them.